Maternal puerperal infection caused by Parabacteroides goldsteinii: a case report - Peng, Liwei; Chen, Xiaomin; Wang, Zhenhui; Yi, Lu; Jin, Zhengjiang (Frontiers in Medicine, 2024)
Background Parabacteroides goldsteinii, a member of the Parabacteroides genus, was initially discovered in the feces and abdominal tissue of patients with appendicitis, peritonitis, and abdominal abscesses. In recent years, P. goldsteinii has been widely regarded as a gut probiotic, and human infections have been extremely rare. In 2010, P. goldsteinii was first isolated from the blood culture of a patient with abdominal infection, confirming its ability to cause bacteremia. In this study, we report a rare case of puerperal infection with septic shock caused by P. goldsteinii infection in a pregnant woman. Case presentation A 31-year-old female experienced perineal lacerations, cervical lacerations, and postpartum hemorrhage during childbirth. Nine days postpartum, the patient developed septic shock, and P. goldsteinii infection was identified through blood culture and mass spectrometry. We administered broad-spectrum antibiotics, including meropenem/nalidixic acid and piperacillin tazobactam, intravenously, but the antimicrobial effect was not satisfactory. Upon ultrasound examination, we identified a focus of infection in the patient’s uterus. Subsequently, uterine curettage was performed, followed by uterine cavity irrigation with metronidazole and intramuscular injection of gentamicin and dexamethasone. Following treatment, the patient’s physiological parameters gradually returned to normal, and she was discharged 30 days after admission. Conclusion Parabacteroides goldsteinii bacteraemia is extremely rare, and clinically, the postinfection toxicity of this bacterium appears to be significant. In this report, we review the research history of P. goldsteinii and relevant infection cases, aiming to enhance awareness among clinical practitioners, particularly obstetricians and gynecologists, regarding P. goldsteinii bloodstream infections, facilitating early diagnosis and timely treatment.